2014
DOI: 10.1093/hmg/ddu514
|View full text |Cite
|
Sign up to set email alerts
|

OCRL-mutated fibroblasts from patients with Dent-2 disease exhibit INPP5B-independent phenotypic variability relatively to Lowe syndrome cells

Abstract: OCRL mutations are associated with both Lowe syndrome and Dent-2 disease, two rare X-linked conditions. Lowe syndrome is an oculo-cerebro-renal disorder, whereas Dent-2 patients mainly present renal proximal tubulopathy. Loss of OCRL-1, a phosphoinositide-5-phosphatase, leads in Lowe patients' fibroblasts to phosphatidylinositol-4,5-bisphosphate (PI(4,5)P2) accumulation, with defects in F-actin network, α-actinin distribution and ciliogenesis, whereas fibroblasts of Dent-2 patients are still uncharacterized. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 54 publications
2
31
1
Order By: Relevance
“…This clinical observation is supported by a recent study on fibroblasts from patients with Lowe syndrome and Dent-2 disease in which Montjean et al [86] demonstrated an intermediate phenotype of Dent-2 fibroblasts in terms of the F-actin network, alpha-actinin, and primary cilia. Of note, PtdIns(4,5)P 2 was elevated in cells from patients with Lowe syndrome and Dent-2 disease, and it did not differ between these groups.…”
Section: Lowe Syndrome or Dent-2 Disease?mentioning
confidence: 59%
See 2 more Smart Citations
“…This clinical observation is supported by a recent study on fibroblasts from patients with Lowe syndrome and Dent-2 disease in which Montjean et al [86] demonstrated an intermediate phenotype of Dent-2 fibroblasts in terms of the F-actin network, alpha-actinin, and primary cilia. Of note, PtdIns(4,5)P 2 was elevated in cells from patients with Lowe syndrome and Dent-2 disease, and it did not differ between these groups.…”
Section: Lowe Syndrome or Dent-2 Disease?mentioning
confidence: 59%
“…Suchy et al reported prenatal diagnosis by measuring PtdIns(4,5)P 2 5-phosphatase activity in cultured amniocytes [85]. However, the lack of genotype–phenotype correlation and the fact that Dent-2 patients and patients with Lowe syndrome have comparable PtdIns(4,5)P 2 5-phosphatase activity [18, 86] limit prenatal diagnosis with respect to disease severity. Other parameters that can be used for prenatal screening are elevated maternal serum and amniotic fluid alpha-fetoprotein [87], or the presence of fetal cataract on ultrasonography images [11].…”
Section: Genetic Counseling and Prenatal Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…However, Dent-2 disease fibroblasts exhibited milder phenotypes than those from LS patient cells. 79 Notably, the levels of PI(4,5)P 2 and Inpp5B were very similar in LS and Dent patient fibroblasts. 79 These results suggest that Inpp5B does not contribute to the milder phenotypes exhibited by the Dent-2 patient fibroblasts and that, in addition to the phosphatase activity, other functions contribute to the phenotypic manifestations seen in patients.…”
mentioning
confidence: 89%
“…56 Most recently, fibroblasts of LS and Dent-2 patients were compared for phenotypic defect. 79 Fibroblasts from both disease groups showed the same category of defects such as lesser F-actin fibers, disorganized α-actinin staining, and ciliogenesis defects. However, Dent-2 disease fibroblasts exhibited milder phenotypes than those from LS patient cells.…”
mentioning
confidence: 92%